2011
DOI: 10.1088/0953-8984/23/11/115502
|View full text |Cite
|
Sign up to set email alerts
|

Band structure of Si/Ge core–shell nanowires along the [110] direction modulated by external uniaxial strain

Abstract: Strain modulated electronic properties of Si/Ge core-shell nanowires along the [110] direction were reported, on the basis of first principles density-functional theory calculations. In particular, the energy dispersion relationship of the conduction/valence band was explored in detail. At the Γ point, the energy levels of both bands are significantly altered by applied uniaxial strain, which results in an evident change of the band gap. In contrast, for the K vectors far away from Γ, the variation of the cond… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 51 publications
3
35
0
Order By: Relevance
“…Various approaches are proposed to tailor the electronic properties of 2D materials and their corresponding nanostructures, which is crucial for their applications in electronics. By virtue of the advantages such as maintaining the materials' properties and effective for single layers, strain engineering is visualized as one of the best possible candidates [14][15][16] and has attracted substantial attention [17][18][19][20][21][22][23][24][25] . Since graphene and plentiful postgraphene 2D materials emerged, studies revealed 2D layered materials have superior mechanical flexibility compared to their bulk counterparts 21,26 .…”
mentioning
confidence: 99%
“…Various approaches are proposed to tailor the electronic properties of 2D materials and their corresponding nanostructures, which is crucial for their applications in electronics. By virtue of the advantages such as maintaining the materials' properties and effective for single layers, strain engineering is visualized as one of the best possible candidates [14][15][16] and has attracted substantial attention [17][18][19][20][21][22][23][24][25] . Since graphene and plentiful postgraphene 2D materials emerged, studies revealed 2D layered materials have superior mechanical flexibility compared to their bulk counterparts 21,26 .…”
mentioning
confidence: 99%
“…Researchers have theoretically demonstrated the modulated band gap by external strains in a variety of systems such as pure Si 17 and Ge 18 and Si/Ge Core-shell nanowires. 19 It would be very interesting to investigate strain effects on the band structure of WZ GaAs nanowires and examine if the direct-indirect band gap transition can be engineered for applications.…”
mentioning
confidence: 99%
“…Several experimental [27,28] and theoretical [29][30][31] investigations have been performed to study of the quantum confinement effects in the Si-Ge core shell nanowires. For instance the Peng et al [22] have studied the band structure properties of the Si-Ge core-shell nanowires in different situations of applied uniaxial strain. Using tight binding approximation Neupane et al [32] have studied the electronic structure of Ge-Si core-shell NCs with considering crescent shape of Ge core.…”
Section: Accepted Manuscriptmentioning
confidence: 99%